Global pharmaceutical care approaches to autism spectrum disorder: a scoping review protocol. - Sape, Relebogile Masekela; Shead, Dorothy Agnes; Maseko, Busisiwe Constance (JBI Evidence Synthesis, 2024)
Objective: The aim of this review is to map the literary evidence on pharmaceutical care approaches and trends being seen globally for the treatment of the signs and symptoms of autism spectrum disorder (ASD). Introduction: ASD is a neurodevelopmental condition synonymous with sliding-scale behavioral, communication, learning, and social problems. Causes include genetic and environmental factors. Pharmaceuticals are prescribed to treat the behavioral patterns of ASD. Inclusion criteria: This review will incorporate studies that report on the pharmaceutical care approaches used to treat the signs and symptoms of ASD as well as to identify the global trends related to their use. Studies not falling under the ASD umbrella will be excluded. All primary, secondary, and gray literature will be included. No language restrictions will be applied. Studies from January 1, 1984, will be included. Methods: This review will be conducted in line with the JBI methodology for scoping reviews and reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. A preliminary search of MEDLINE (PubMed) will be followed by searches of Emcare (Ovid), Nursing and Allied Health Premium (ProQuest), and Google Scholar. Two independent reviewers will screen titles and abstracts and extract data from selected sources. A third reviewer will adjudicate any conflicts until consensus is reached. The findings will be presented in a narrative summary with accompanying gap maps, figures, and tables.